(untitled) (Rajarshi Janak University Research Journal, 2025)
This paper reads the eco-consciousness in visual social semiotics of Mithila Painting. The visual as the lively example of social semiotics is a great form of traditional and contemporary art. Along with the changes in the perspectives of the people, the traditional religion and myth dominated paradigm of Mithila Painting has shifted from mytho-cultural to politico-environmental issues. It has become influential way of making people aware of the contemporary issues. This shift in its traditional aesthetics has contributed to the awareness of the people about the environment, politics, female subjectivity etc. The legacy of Mithila painting is based on the idea of fertility, life cycle and the nature. There is the remarkable use of the natural motifs in the Mithila works of art, which are the essential part of entire ecology, environment and ecosystem. The relation between human and nature is the common theme of Mithila Painting since then to now. This consciousness about the environment, ecology and ecosystem has explicitly come into practice in the contemporary time though it was in dormant stage in the traditional forms. The use of the bamboo, lotus, natural colors, animals, pond all signifies the eco-conscious aspect of Mithila Painting.